Activation of Pancreatic Stellate Cells Is Beneficial for Exocrine but Not Endocrine Cell Differentiation in the Developing Human Pancreas - Li, Jinming; Chen, Bijun; Fellows, George F.; Goodyer, Cynthia G.; Wang, Rennian (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic stellate cells (PaSCs) are non-endocrine, mesenchymal-like cells that reside within the peri-pancreatic tissue of the rodent and human pancreas. PaSCs regulate extracellular matrix (ECM) turnover in maintaining the integrity of pancreatic tissue architecture. Although there is evidence indicating that PaSCs are involved in islet cell survival and function, its role in islet cell differentiation during human pancreatic development remains unclear. The present study examines the expression pattern and functional role of PaSCs in islet cell differentiation of the developing human pancreas from late 1st to 2nd trimester of pregnancy. The presence of PaSCs in human pancreata (8-22 weeks of fetal age) was characterized by ultrastructural, immunohistological, quantitative RT-PCR and western blotting approaches. Using human fetal PaSCs derived from pancreata at 14-16 weeks, freshly isolated human fetal islet-epithelial cell clusters (hIECCs) were co-cultured with active or inactive PaSCs in vitro. Ultrastructural and immunofluorescence analysis demonstrated a population of PaSCs near ducts and newly formed islets that appeared to make complex cell-cell dendritic-like contacts. A small subset of PaSCs co-localized with pancreatic progenitor-associated transcription factors (PDX1, SOX9, and NKX6-1). PaSCs were highly proliferative, with significantly higher mRNA and protein levels of PaSC markers (desmin, αSMA) during the 1st trimester of pregnancy compared to the 2nd trimester. Isolated human fetal PaSCs were identified by expression of stellate cell markers and ECM. Suppression of PaSC activation, using all-trans retinoic acid (ATRA), resulted in reduced PaSC proliferation and ECM proteins. Co-culture of hIECCs, directly on PaSCs or indirectly using Millicell Inserts or using PaSC-conditioned medium, resulted in a reduction the number of insulin+ cells but a significant increase in the number of amylase+ cells. Suppression of PaSC activation or Notch activity during the co-culture resulted in an increase in beta-cell differentiation. This study determined that PaSCs, abundant during the 1st trimester of pancreatic development but decreased in the 2nd trimester, are located near ductal and islet structures. Direct and indirect co-cultures of hIECCs with PaSCs suggest that activation of PaSCs has opposing effects on beta-cell and exocrine cell differentiation during human fetal pancreas development, and that these effects may be dependent on Notch signaling.